ADMINISTRATION SERVICE EFFECTIVENESS AT PPS STIA BINA TARUNA GORONTALO - Sri Rahmatia Ali; Frista Iin Wahyuni; Siske Anani (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to analyze and to determine the effectiveness of financial administration services at PPs STIA Bina Taruna Gorontalo. This research uses descriptive qualitative method. The informants of this study were students and employees at PPs STIA Bina Taruna Gorontalo. Data collection through interviews. The results showed that the administrative services at the Postgraduate Campus of STIA Bina Taruna Gorantalo were running effectively. This can be seen from the five dimensions of service quality, namely tangible or very good physical appearance of employees, employee reliability is very reliable, employee responsiveness is very fast, assurance or assurance is running well and empathy is well manifested.